Human Haptic Perception Basics and Applications - Grunwald, Martin (Birkhäuser Basel : Imprint: Birkhäuser, 2008)
Active touch perception - also known as haptic perception - is of primary importance for the planning, direction and execution of everyday actions. This most complex of human sensory systems is gaining ever more importance for various scientific disciplines as well as practical industrial applications. In this book an international team of 80 authors presents a comprehensive collection of writings on both aspects of research on human haptic perception. After a theoretical and historical introduction, the chapters are dedicated to neurophysiological basics as well as the psychological, clinical and neuropsychological aspects of haptic perception. Results of studies into human haptic perception in the fields of virtual haptics and robotics are also included. In the final section, contributions from the applied and industrial sectors illustrate the practical uses of knowledge about the human sense of touch. This easily accessible textbook gives not only students, scientists and those with prior knowledge, but also interested laypersons insights into a fascinating area of study that is constantly discovering new challenges and presenting innovative solutions.